Perfectionism and coping with stress in Venezuelan adults - Aguilar Durán, Leonardo Andrés (2024)
This research studied the predictive power of perfectionism (from the perspective of Frost et al., 1990) and some demographic variables on the different stress coping styles (according to the model described by Roger et al., 1993) in adults from Venezuela. The design was cross-sectional predictive. Participants were 510 Venezuelans, 79.2 % women and 20.8 % men, with an average age of 42.76 years (+/− 12.73), mostly residents of the interior of the country (72.2 %), with university education (70.6 %), and paid work (75.7 %). The instruments used were adapted versions of the Multidimensional Perfectionism Scale and the Coping Style Questionnaire. Rational coping (the most used by the participants) was predicted by personal standards, organization, parental expectations, low levels of fear of mistakes, and being male. Emotional coping (the least used) was predicted by fear of mistakes, a younger age, and lower levels of education. Predictions for detached and avoidance coping were weak. Certain relationships (e. g. in which personal standards are involved) could be modulated by third variables. In conclusion, the results found support the appreciation of the rational coping style as fundamentally adaptive and the emotional style as maladaptive, a differentiation in which perfectionism as a personality trait is involved.